Printed light-trapping nanorelief Cu electrodes for full-solution-processed flexible organic solar cells. (22nd July 2016) - Li, Kan; Zhang, Yaokang; Zhen, Hongyu; Niu, Liyong; Fang, Xu; Liu, Zhike; Yan, Feng; Shen, Weidong; Li, Haifeng; Zheng, Zijian
Abstract: Light-trapping nanorelief metal electrodes have been proven to be an effective approach to improve the absorption performance of flexible organic solar cells (FOSCs). These nanorelief electrodes have been made by conventional vacuum deposition techniques, which are difficult to integrate with roll-to-roll fabrication processes. To address this challenge, this paper reports, for the first time, the fabrication of highly conductive nanorelief Cu electrodes on the flexible substrates through solution printing and polymer-assisted metal deposition at room temperature in the air. FOSCs made with these printed nanorelief Cu electrodes possess not only much improved power conversion efficiency, by 13.5%, but also significant enhancement in flexibility when compared with those made with flat Cu electrodes. Because of the low material and fabrication cost, these printed nanorelief Cu electrodes show great promise in roll-to-roll fabrication of FOSCs in the future.